Gender Disparity in Work Participation: A Comparative Study of Varanasi District, U.P. - Kushawaha, Shailendra; Sharma, V.N. (National Geographical Journal of India, 2022)
In India, female comprises 48% of the total population but their participation in economic activities is only 25% in comparison to 53.20% participation of male, which shows the high disparity in work participation. It is very necessary to provide equal opportunity to all women, to participate in economic activities to boost up our economy, improving their living standards and all types of nutritional support to the family. This paper is an attempt to analyze gender disparity in work participation comparing rural and urban populations in Varanasi district. To analysis, the gender disparity in work participation, block-level gender disparity has been calculated using the Crude Work Participation rate and Sopher Disparity Index(D). The results show that each block has a high gender disparity, and comparatively urban areas have higher gender disparity index than that of rural, due to patriarchal mindset, unsafe work environment, and unequal job opportunities, etc